Comparisons of Annual No‐Till Spring Cereal Cropping Systems in the Pacific Northwest. Issue 1 (12th June 2015) - Young, Frank L.; Alldredge, J. R.; Pan, William L.; Hennings, Curtis
Abstract : Winter wheat ( Triticum aestivum L.)– summer fallow (WWF) has been the prevalent rotation in the low rainfall zone of the Pacific Northwest (PNW) for more than 130 years; however, this rotation is characterized by poor soil health, high pest incidence, and poor environmental sustainability. A 6‐year study was initiated in 1995 to evaluate the agronomic and economic feasibility of no‐till spring cereal cropping systems to replace or supplement fallow. The systems included: WWF; no‐till spring wheat‐chemical fallow (SWChF); continuous no‐till hard red spring wheat (CHRSW); and no‐till hard red spring wheat– no‐till spring barley (HRSWSB). Overall the WWF (reduced tillage fallow) system produced 25% more grain, almost $30/rotational acre more net return and was less risky compared to the second best (SWChF) system. This research was the first ever to examine a SWChF system. This system yielded higher than both the CHRSW and HRSWSB in all but 1 year. In general, HRSW yielded similarly for both systems. The 2000–2001 crop growing season was extremely dry and crop yields for that year were from 45 to 80% less than their respective 5‐year average, depending on the crop. Although all of the no‐till spring cropping systems provided greater wind erosion protection, the economic returns were negative for the duration of the study. Perhaps if compensation was provided to growers for conservation practices, adoption of these agronomically and environmentally sound systems would be readily adopted.